2020
DOI: 10.5817/pc2020-2-178
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Corporatism in States Governed by Populist Political Parties: The Cases of Poland and Hungary

Abstract: Between 1945 and 2010 three main types of corporatism were discussed in the political science literature: the ‘classic’ and ‘lean’ corporatism that existed in the West European countries and the ‘illusory’ corporatism that dominated in Central and Eastern Europe after 1989. The aim of the paper is to examine whether a new version of corporatism, which I call ‘patronage’ corporatism, emerged in Hungary and Poland during the first term of the governments formed by populist political parties (in Hungary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…However, unlike Maloney et al (2018), we found EU funding to be less important for professionalization than support from national governments. In line with Fraussen (2014) and Olejnik (2020), our data indeed show a 'visible hand' of the state in promoting organizational professionalization.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, unlike Maloney et al (2018), we found EU funding to be less important for professionalization than support from national governments. In line with Fraussen (2014) and Olejnik (2020), our data indeed show a 'visible hand' of the state in promoting organizational professionalization.…”
Section: Discussionsupporting
confidence: 91%
“…However, there has been a recent boom in analyses of organized interests in the region. Scholars have covered, among other things, population ecologies Rozbicka and Kamiński, 2021) and advocacy strategies (Rozbicka et al, 2020;Czarnecki, 2021), while also exploring state-interest group interactions (Ost, 2011;Olejnik, 2020;Dobbins and Riedel, 2021) and lobbying regimes (Vargovčíková, 2017;Rozbicka et al, 2020). Most recently, observers have also produced studies on the concrete impact of organized interests on policymaking (Horváthová and Dobbins, 2019;Rozbicka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While scholars have made some headway in addressing corporatist interest intermediation in post-communist economic policy-making (Jahn 2016;Avdagic 2005;Olejnik 2020;Ost 2000), advocacy patterns in other areas remain largely underresearched. Corporatism is a standard analytical paradigm in political science, which grasps systematized negotiations between major social partners.…”
Section: State Of the Artmentioning
confidence: 99%
“…He classifies them as "patronage corporatist" to the extent that they purportedly actively divide organized interests into allies required for reaching political objectives and hostile organizations lacking the "necessary moral authority to advocate for the interests of the citizenry" (Olejnik 2020, 184). Accordingly, governments tend to only engage in political consultations and exchange with social partners with coinciding interests, many of whom often receive government funding, while rivalling organizations are actively discredited and combatted (Olejnik 2020).…”
Section: Previous Work On Post-communist Interest Intermediationmentioning
confidence: 99%